PENEBANGAN POHON YANG EFISIEN DENGAN KERUSAKAN TEGAKAN TINGGAL MINIMAL - Sukadaryati Sukadaryati; Dulsalam Dulsalam (Jurnal Penelitian Hasil Hutan, 2002)
To accomplish natural forest sustainable. the Indonesian Selective Culling and Planting (ISCP) system is adopted for natural forest management and timber harvesting. Felling trees using controlled system, based on ISCP guidelines. is able to decrease the level of residual stand damage. An investigation on a more efficient treefelling with minimum residual stand damage was carried out at on logging company in Jambi in 2000. The object is to obtain information on working time. productivity offelling and residual stand damage.The investigation results revealed that the level of residual stand damage caused by conventionalfelling system ranged from 12 0-18.3% with an average of 15.3%. and by controlled system varied from 7. 7-12. 9% with an average of 9. 9%. Controlled harvesting system could decrease the residual stand damage of 5.4%. The productivity of conventional felling system ranged from 24.465-44.873 m3/hour with an average of 33.681 m3/hour. Productivity of controlled felling system varied from 16.883-35. 650 m3/hour with an average of 25.012 m3/hour. The productivity of controlled felling system was lower than conventional felling system. For ecological and sustainability reasons, controlled felling system is more promising. PENEBANGAN POHON YANG EFISIEN DENGAN KERUSAKAN TEGAKAN TINGGAL MINIMAL